Sex differences in risks of in-hospital and late outcomes after cardiac surgery: a nationwide population-based cohort study. Issue 2 (2nd February 2022) - Chang, Feng-Cheng; Chen, Shao-Wei; Chan, Yi‐Hsin; Lin, Chia-Pin; Wu, Victor Chien-Chia; Cheng, Yu-Ting; Chen, Dong-Yi; Hung, Kuo-Chun; Chu, Pao-Hsien; Chou, An-Hsun
Abstract : Objectives: Outcomes of sex differences in major cardiac surgery remain controversial. A comprehensive understanding of sex differences in major adult cardiac surgery could provide better knowledge of risk factors, management strategy and short-term or long-term outcomes. The present study aimed to investigate sex differences in the risks of outcomes of major cardiac surgeries and subgroup analyses of different valve types. Design: Population-based nationwide cohort study. Setting: Data were obtained from National Health Insurance Research Database (NHIRD) in Taiwan. Participants: A total of 66 326 adult patients (age ≥20 years; 30.3% women) who underwent a first major cardiac surgery (isolated coronary artery bypass graft (CABG), isolated valve or concomitant bypass/valve) from 2000 to 2013 were identified via Taiwan NHIRD. Main outcome measures: Outcomes of primary interest were in-hospital death and all-cause mortality during follow-up period. Propensity score matching was conducted as a secondary analysis for the sensitivity test. Results: Women who underwent isolated CABG tended to have greater risks of both in-hospital (OR 1.37; 95% CI 1.26 to 1.49) and late outcomes (HR 1.26; 95% CI 1.22 to 1.31). Women after concomitant CABG/valve also had a greater in-hospital (OR 1.19; 95% CI 1.01 to 1.40) and long-term mortality (HR 1.14; 95% CI 1.05 to 1.24). Women after isolated mitral valve repair have a non-favourable outcome of in-hospital mortality (OR 1.70; 95% CI 1.01 to 2.87). Women who did not receive an isolated aortic valve replacement had more favourable all-cause mortality outcome (HR 0.90; 95% CI 0.84 to 0.96). Secondary analysis in the propensity score-matching cohort demonstrated results similar to the primary analysis. Conclusions: Female patients who underwent procedures involving CABG (with or without concurrent valvular intervention) had generally worse outcomes. However, the results of isolated valve surgery were variable on the basis of the type of intervened valve.